The Code, the Consumer, and the Institutional Structure of the Common Law - Edward L. Rubin (Washington University Law Quarterly, 1997)
This Article argues that the enforcement mechanism that was unthinkingly embodied in the UCC severely disadvantages consumers in their effort to obtain the legal remedies that the UCC itself provides.
Keywords: Commercial law; Consumer protection; Common law